Assesmenf of T.B Patients, Relation between their knowledge of disease and therapeutic regimers in TB/Controlcenter, Tehran, 1377 (Tehran University of Medical Sciences, 2000)
"nThis research is a descriptive- analytic study which has been conducted in"norder to determine the degree of tuberculous patients knowledge of their tubereulosis disease and its relation to therapeutic regimen in Tehran TB control centers."nIn this research , 120 tuberculous patients calling on tuberculosis control centers in Tehran and being under drug therdpyfor about 2-9 months were selected as subjects in this research . sampling has been easy as well as haphazardly data was gathered through a questionnaire. the questionnaire used in this research includes 3 section . After gathering the data, descriptive and deductive statistics used in order to analyse the data more over, chi-square and fisher Exact Test used to study the relation between the knowledge variables and therapeutic regimen in accordance with demographic characteristics and chouporof coefficient used to determine correlation intensity."nResearch results concerning units under investigation showed that the majority on insufficient knowledge of their disease which the minority (%18) had a sufficient knowledge, the majority (%62) had a proper drug therapy while the minority (%1) did not the majority (%72) did not Take a efficient diet while the minority (%2) took a proper diet, the majority (%58) medium personal Health care while the minority (%15) folllowed a good personal health care, and generally the majority (%47) had a medium therapeutic regimen while the minority (%11) did not have sufficient"nRegarding the relation between the degree of knowledge and thrapeutic therapy which was the main objective in this research,the result ofperson,s correlation coefficient (z= 7.88, r-o.62 jshowed a direct correlation in such a manner that the degree of knowledge will increase with quality of therapeutic regimen.